Daily Consumption of Synbiotic Yogurt Decreases Liver Steatosis in Patients with Nonalcoholic Fatty Liver Disease: A Randomized Controlled Clinical Trial. Issue 8 (20th June 2018) - Bakhshimoghaddam, Farnush; Shateri, Kamran; Sina, Morad; Hashemian, Maryam; Alizadeh, Mohammad
Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease in developed and developing countries. The use of synbiotics has been proposed as a probable management strategy for patients with NAFLD. Objective: We investigated the effects of synbiotic yogurt on hepatic steatosis and liver enzymes as primary outcomes and on oxidative stress markers, adipokine concentration, and gut peptide concentration as secondary outcomes in patients with NAFLD. Methods: In this 24-wk, open-label, randomized controlled clinical trial, 102 patients [50 men and 52 women; mean age: 40 y; body mass index (in kg/m 2 ) (mean ± SD): 31.2 ± 4.9] were randomly assigned to 3 groups, including 2 intervention groups and 1 control group. The intervention groups consumed 300 g synbiotic yogurt containing 10 8 colony-forming units Bifidobacterium animalis /mL and 1.5 g inulin or conventional yogurt daily and were advised to follow a healthy lifestyle (i.e., diet and exercise). The control group was advised to follow a healthy lifestyle alone. We evaluated differences between groups in liver function measures by using repeated-measures ANOVA, ANCOVA, and logistic regression. Results: At the end of the study, the grades of NAFLD, as determined by ultrasonography, showed a significant decrease in the synbiotic group compared with the conventional and control groups ( P < 0.001). The following significant mean ± SD decreases were seen in the synbiotic, conventional, and control groups, respectively: serum concentration of alanine aminotransferase (−14.5 ± 15.6 compared with 4.6 ± 15.4 and 3.1 ± 14.4 IU/L; P = 0.008), aspartate aminotransferase (−7.5 ± 6.1 compared with 3.0 ± 8.2 and 3.1 ± 5.7 IU/L; P < 0.001), alkaline phosphatase (−26.2 ± 16.8 compared with 3.4 ± 30.1 and 1.5 ± 31.9 IU/L; P = 0.024), and γ-glutamyltransferase (−6.0 ± 6.0 compared with 1.0 ± 6.4 and 7.6 ± 11.4 IU/L; P < 0.001). Conclusion: Synbiotic yogurt consumption improved hepatic steatosis and liver enzyme concentrations in patients with NAFLD. This trial was registered at the Iranian Registry of Clinical Trials website (www.irct.ir ) as IRCT2017020932417N2.